PENINGKATAN KETERAMPILAN SENAM LANTAI MELALUI MODEL PROBLEM BASED LAERNING PADA PESERTA DIDIK KELAS VII SMP NEGERI 13 BANJARBARU - M. Khairin Fazri; Perdinanto; Ahmad Syarif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study sought to enhance seventh-grade students' floor gymnastics skills at SMP Negeri 13 Banjarbaru through the application of the Problem Based Learning (PBL) approach. The employed research methodology was Classroom Action Research (CAR), executed in two cycles comprising planning, action implementation, observation, and reflection stages. This study involved 31 students as subjects. The methods of data collecting comprised observation, skills assessments, and documenting. The findings indicated that the application of the Problem-Based Learning methodology enhanced students' floor gymnastics abilities. During the pre-cycle phase, the mean student skill score was 61.29, classified as adequate. Following the deployment of the PBL model in Cycle I, the average score rose to 74.19, classified as good. In cycle II, the average score rose to 76.67, which is also classified as good. The PBL methodology enhanced students' skills while simultaneously augmenting their engagement, confidence, collaboration, and participation in the learning process. Consequently, the Problem-Based Learning methodology is seen beneficial in enhancing floor gymnastics skills within physical education instruction.